Analisis SWOT dalam Menentukan Strategi Pemasaran Produk UMKM Opak Kolontong - Ade Ponirah; Resna Yuliana; Ade Iskandar Nasution (Fakultas Ekonomi dan Bisnis Islam, 2021)
Management strategy as an art and science to formulate, implement, and evaluate organizational decisions to achive its goals. The marketing strategy that has been implemented by the UMKM Opak Kolontong in Bojongkunci Village still uses a traditional system that is by supplying to the center for souvenirs in Bandung. This product has the power that is not fast stale without using preservatives. This product olso has a disadvantage of not having a store and less attractive roughness. The opportunity for this product is to do promotions using instagram and flavor. The threat of this product is the low sales level.